Analisis Metode Pembelajaran Sejarah Kebudayaan Islam di Madrasah Tsanawiyah Negeri 3 Kota Banjarmasin - Muhammad Ferdy Hidayat; Raihanah Raihanah (MAN 4 Kota Pekanbaru, 2026)
This study analyzes the implementation of Islamic Cultural History (SKI) learning methods at Madrasah Tsanawiyah Negeri 3 Banjarmasin and the factors influencing their effectiveness. Using a descriptive qualitative approach, the research involved the head of the madrasah, SKI teachers, and 40 students, with data collected through observation, interviews, and documentation. Findings reveal that SKI learning remains dominated by the lecture method with limited media use, resulting in low student motivation and participation. Contributing factors include short class time, non-linear teacher backgrounds, limited pedagogical competence, inadequate media utilization, and less effective classroom management. Students expressed higher interest in interactive approaches such as discussion, role playing, and multimedia. The study suggests diversifying methods, integrating technology-based media, and enhancing teacher competence to foster engagement and align SKI learning with the Merdeka Curriculum.